2021
DOI: 10.1038/s41598-021-86222-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trifocal or hybrid multifocal-extended depth of focus intraocular lenses: a systematic review and meta-analysis

Abstract: This meta-analysis aimed to evaluate the clinical outcomes following implantation of trifocal intraocular lenses (IOLs) or a hybrid multifocal-extended depth of focus (EDOF) IOL in cataract or refractive lens exchange surgeries. We examined 13 comparative studies with bilateral implantation of trifocal (898 eyes) or hybrid multifocal-EDOF (624 eyes) IOLs published through 1 March 2020. Better uncorrected and corrected near visual acuity (VA) were observed in the trifocal group (MD: − 0.143, 95% CI: − 0.192 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…Therefore, it is indicated the postoperative level in dependence for near vision was possibly higher in the EDOF IOLs than the diffractive MIOLs. It is also consistent with the fact that EDOF IOLs, with an extended far focus area which reaches to the intermediate distance, restore distance and intermediate visual function but with restraint of near vision ( 27 29 ). In Ferreira et al's study ( 21 ), more patients implanted with EDOF IOLs were free from glasses than those receiving monofocal IOLs.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it is indicated the postoperative level in dependence for near vision was possibly higher in the EDOF IOLs than the diffractive MIOLs. It is also consistent with the fact that EDOF IOLs, with an extended far focus area which reaches to the intermediate distance, restore distance and intermediate visual function but with restraint of near vision ( 27 29 ). In Ferreira et al's study ( 21 ), more patients implanted with EDOF IOLs were free from glasses than those receiving monofocal IOLs.…”
Section: Discussionsupporting
confidence: 85%
“…It has been reported in different clinical studies that trifocal IOLs can improve distance and near vision while providing a good level of intermediate vision. This type of IOL has been reported to produce less limitation in visual function and less spectacle dependence than seen in patients implanted with bifocal or monofocal IOLs [ 1 , 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different designs have been launched on the market and are available for consideration by cataract and refractive surgeons. Some reviews have shown that the use of trifocal IOLs in cataract patients improves intermediate visual acuity compared to patients implanted with bifocal IOLs [ 1 , 2 , 3 ]. The addition of a third focus, specifically designed to enhance intermediate vision, compared to classic bifocal designs has increased the use of trifocal IOLs among surgeons aiming to provide their patients with a better visual performance over the entire range of distances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trifocal intraocular lens (IOL) implantation in patients submitted to cataract or clear lens surgery has improved the visual outcomes at different distances, from far to near, expanding the range of useful vision and allowing spectacle independence. The benefit of using these lenses in terms of visual performance has been pointed out in several systematic reviews and meta-analysis, where the improvement in visual acuity at intermediate distance is considerable better than that found in patients implanted with bifocal lenses [ 1 3 ]. Given the increasing amount of time that people over the age of 45 spend on activities that require intermediate vision, such as computer work or cooking, there is an increasing number of patients implanted with these lenses around the world who improve intermediate vision while maintaining distance vision.…”
Section: Introductionmentioning
confidence: 99%